Synthesis of Magnetic Base Catalyst from Industrial Waste for Transesterification of Palm Oil - Shamala Gowri Krishnan; Fei-Ling Pua; Hong-Hua Lim (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Industrial waste is produced in large amounts annually; without proper planning, the waste might cause a serious threat to the environment. Hence, an industrial waste-based heterogeneous magnetic catalyst was synthesized using carbide lime waste (CLW) as raw material for biodiesel production via transesterification of palm oil. The catalyst was successfully synthesized by the one-step impregnation method and calcination at 600 °C. The synthesized catalyst, C-CLW/g-Fe2O3, was characterized by temperature-programmed desorption of carbon dioxide (CO2-TPD), scanning electron microscopy (SEM), electron dispersive X-ray spectroscopy (EDX), X-ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), vibrating sample magnetometer (VSM), and Fourier transform infrared spectroscopy (FT-IR). The catalyst has a specific surface area of 18.54 m2/g and high basicity of 3,637.20 µmol/g. The catalytic performance shows that the optimum reaction conditions are 6 wt% catalyst loading, 12:1 methanol to oil molar ratio with the reaction time of 3 h at 60 °C to produce 90.5% biodiesel yield. The catalyst exhibits good catalytic activity and magnetism, indicating that the CLW can be a potential raw material for catalyst preparation and application in the biodiesel industry. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).